THE COMPOSITION OF THE NATIONAL ASSEMBLY OF SERBIA: CHALLENGES AND OBSTACLES - Pejić, Irena (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
Given that political parties participate in the formation, structuring and activity of the parliament, their presence has produced a double impact on the National Assembly of Serbia in the past three decades. On the one hand, their influence has been reflected in the internal structure and efficiency of parliamentary work, while on the other hand, the party system combined with the electoral model left its mark on the manner of political representation. The focus of the paper will be on the impact the political parties had made on the national assembly in the Republic of Serbia, i.e. their influence on the internal organization of the Assembly and consequences on the effectiveness in the parliamentary process. The main goal is to explore the normative framework and parliamentary practice regarding the real possibilities of the National Assembly in fulfilling the basic postulates for the realization of effective national representation. The main question is whether the Assembly, based on its constitutional autonomy, is able to achieve the goals of the “working parliament” and the political representation of all citizens? The problem develops around the extent to which the people’s representation is capable of exercising its constitutional functions if it does not support and protect the differentiated political will of the people. The aim is to point out the possibilities provided by the normative framework, as well as the need for successful parliamentary practice in the realization of parliamentary autonomy. Parliamentary autonomy is necessary not only for the sake of good internal organization and the effectiveness in the parliamentary process but also externally, in strengthening the National Assembly position towards the holders of executive power. The subject of the analysis will be the activities of political parties in the parliament through parliamentary groups and parliamentary committees, as well as a lack of parliamentary opposition guarantees.